Evaluation of Nurses’ Skills about Management of Psychiatric Patients in Emergency Unit - Basim Karim Abd Al Jasim Al Mansory. Qahtan Qasem Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The emergency department (ED) is a health-care location where patients receive treatment for a range of diseases, including life-threatening crises, acute sickness and injury, and chronic-condition problems. Emergency departments (EDs) have the responsibility of providing safe emergency health care to everyone who require it in a compassionate and cost-effective manner Material and Method: A descriptive analytic design was conducted on Evaluation of Nurses’ Skills about Management of Psychiatric Patients in Emergency Unit in Babylon governorate for the period of (December 12th, 2021 to march 14th, 2022). The study instrument was designed to meet the objectives of the current study, which was consisting of two parts: the first part includes the demographical data for nurses; the second part includes the Skills management Scale 37 items (SPSD). Results: The results showed that nurses are young with age (27.89±6.291 year) in which 75.8% of them are seen with age group of 20-29 year. The analysis of skill in this study showed that nurses have fair level of skills as seen among 78.8% and 17.4% among nurse have poor level of skills and 3.8% among nurse have good level of skill. Conclusion: The study concluded that most nurses have a fair level of skills ’ about the treatment of psychiatric disorders at emergency units.